PENGARUH BRAND IMAGE DAN BRAND AMBASSADOR TERHADAP MINAT PEMBELIAN : STUDI KASUS PADA PENGGUNA APLIKASI TIKTOK SHOP DI KALANGAN - Oktaviani, Via; Haji, Son; Purwanto, Purwanto (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to determine the influence of brand image and brand ambassadors on purchasing interest among TikTok Shop app users, particularly among the 2021 cohort of students at Panca Sakti University in Bekasi. TikTok Shop, as a rapidly growing e-commerce platform, leverages the visual appeal and promotional power of brand ambassadors to build a strong brand perception among the younger generation. This study employs a quantitative approach with an associative causal research design. A questionnaire as a data collection method was sent by the researcher to Management students at Panca Sakti University Bekasi who had used the TikTok Shop app. The results of the study indicate that brand image has a positive influence on purchase intent. Brand ambassadors also influence purchase intent among TikTok Shop app users among Management students of the 2021 cohort at Panca Sakti University Bekasi. Brand image and brand ambassadors account for 24.5% of the influence on purchase intent among TikTok Shop app users among Management students of the 2021 cohort at Panca Sakti University in Bekasi, while the remaining 75.5% is influenced by other variables not examined in this study.